Running biomechanics and performances of people with leg amputations - Kram, R. (International Calgary Running Symposium, August 14-17, 2014, 2014)
The Olympic level performances of sprinters with leg amputations has captivated the public and scientists. Sprinters using leg prostheses have rapid swing times and stride frequencies but generate smaller peak ground reaction forces and have longer contact times with their prosthesis equipped legs. Passive-elastic leg prostheses are substantially lighter than biological legs but have fixed spring stiffnesses. Thus, overall leg stiffness cannot be modulated with speed. I interpret these biomechanical differences as indicating compensations for limitations imposed by prostheses. Others suggest that leg prostheses somehow facilitate sprinting performance beyond what individuals could achieve with biological legs. Our understanding of the effects of unilateral amputation on sprinting performance is only nascent and we know even less about athletes with bilateral leg amputations. In contrast, distance running performances by people with leg amputations are nowhere near Olympic levels. Running economy, a key determinant of distance-running performance, is remarkably similar in people with or without unilateral leg amputations. Why do the distance running performances of people with leg amputations lag behind? One possibility is that pain occurring at the residual limb/socket interface impairs performance or moreover limits the tolerable training intensity and volume. Physiological profiles of outstanding distance runners with leg amputations are needed. Improving passive-elastic and developing powered active/passive hybrid leg prostheses are active areas of research. Comparisons between runners with and without amputations continue to help us understand the fundamental factors that limit running performance in all people.